2013
DOI: 10.5732/cjc.012.10219
|View full text |Cite
|
Sign up to set email alerts
|

The recurrence and survival of oral squamous cell carcinoma: a report of 275 cases

Abstract: Oral squamous cell carcinoma (OSCC) is a common malignant tumor of the head and neck, and recurrence is an important prognostic factor in patients with OSCC. We explored the factors associated with recurrence of OSCC and analyzed the survival of patients after recurrence. Clinicopathologic and follow-up data of 275 patients with OSCC treated by surgery in the Cancer Institute and Hospital of Tianjin Medical University between 2002 and 2006 were analyzed. Recurrence factors were analyzed with Chi-square or Fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
198
5
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(214 citation statements)
references
References 11 publications
8
198
5
3
Order By: Relevance
“…male to female ratio of head and neck squamous cell carcinoma is 1.9:1 with most commonly affected age group being 6 th decade. 17 Pre treatment thrombocytosis has proven to be an independent prognostic factor for poor outcome which was observed in our study. Recurrence of tumor was noted in 7cases.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…male to female ratio of head and neck squamous cell carcinoma is 1.9:1 with most commonly affected age group being 6 th decade. 17 Pre treatment thrombocytosis has proven to be an independent prognostic factor for poor outcome which was observed in our study. Recurrence of tumor was noted in 7cases.…”
Section: Discussionsupporting
confidence: 64%
“…18 Post-operative tumor recurrence leads to high morbidity & mortality. 17 High platelet count & poor tumor differentiation, presence of vascular invasion, regional & distant metastasis are poor prognostic factors in patient of head & neck squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…5 The main challenge is that HPV infection is largely asymptomatic or causes only minor lesions. Discovery of HPVpositive oral HNSCC usually occurs at advanced stages, when extensive local invasions and metastasis could prevent complete surgical removal, leading to high recurrence rate and low 5-year survival rate.…”
Section: Tim-3-expressing Macrophages Are Functionally Suppressed Andmentioning
confidence: 99%
“…Interestingly, Chen et al also observed a higher prevalence of earlier stages among women, as well as an association between the presence of IL-6 tumor cytosolic, female gender and lymph node metastasis, demonstrating that other independent factors may also be involved in differences of metastasis risk between genders. It is possible that similar rates of lymph node metastasis may be correlated with similar disease survival curves when comparing men and women, since the N stage is one of the most important prognostic factors in oral cancer 12,13 .…”
Section: Discussionmentioning
confidence: 99%